Pathology in Irish medical education. Issue 1 (22nd August 2019) - Humphreys, Hilary; Stevens, Niall; Leddin, Desmond; Callagy, Grace; Burke, Louise; Watson, R William; Toner, Mary
Abstract : Pathology is the study of disease and is an important component in medical education. However, with medical curriculum reform, its role and contribution to medical courses is under potential threat. We surveyed the status of pathology in all six Irish medical schools. Information was received from five direct undergraduate and four graduate entry programmes. Pathology was recognisable as a core subject in all but one of the medical schools, was generally taught in years two or three, and the greatest contact hours were for histopathology (44–102 hours). Lectures were the most common teaching modality, and all used single best or extended matching answer multiple-choice questions as part of assessments. Currently, pathology is very visible in Irish medical education but needs to remain relevant with the move to theme and case-based teaching. There is heavy reliance on lectures and on non-academic/full-time hospital staff to deliver teaching, which may not be sustainable.